Head-to-head trial of pegunigalsidase alfa versus agalsidase beta in patients with Fabry disease and deteriorating renal function: results from the 2-year randomised phase III BALANCE study - Wallace, Eric L; Goker-Alpan, Ozlem; Wilcox, William R; Holida, Myrl; Bernat, John; Longo, Nicola; Linhart, Aleš; Hughes, Derralynn A; Hopkin, Robert J; Tøndel, Camilla; Langeveld, Mirjam; Giraldo, Pilar; et al. (Journal of medical genetics, 2024)
BACKGROUND: Pegunigalsidase alfa is a PEGylated α-galactosidase A enzyme replacement therapy. BALANCE (NCT02795676) assessed non-inferiority of pegunigalsidase alfa versus agalsidase beta in adults with Fabry disease with an annualised estimated glomerular filtration rate (eGFR) slope more negative than -2 mL/min/1.73 m2/year who had received agalsidase beta for ≥1 year. METHODS: Patients were randomly assigned 2:1 to receive 1 mg/kg pegunigalsidase alfa or agalsidase beta every 2 weeks for 2 years. The primary efficacy analysis assessed non-inferiority based on median annualised eGFR slope differences between treatment arms. RESULTS: Seventy-seven patients received either pegunigalsidase alfa (n=52) or agalsidase beta (n=25). At baseline, mean (range) age was 44 (18-60) years, 47 (61%) patients were male, median eGFR was 74.5 mL/min/1.73 m2 and median (range) eGFR slope was -7.3 (-30.5, 6.3) mL/min/1.73 m2/year. At 2 years, the difference between median eGFR slopes was -0.36 mL/min/1.73 m2/year, meeting the prespecified non-inferiority margin. Minimal changes were observed in lyso-Gb3 concentrations in both treatment arms at 2 years. Proportions of patients experiencing treatment-related adverse events and mild or moderate infusion-related reactions were similar in both groups, yet exposure-adjusted rates were 3.6-fold and 7.8-fold higher, respectively, with agalsidase beta than pegunigalsidase alfa. At the end of the study, neutralising antibodies were detected in 7 out of 47 (15%) pegunigalsidase alfa-treated patients and 6 out of 23 (26%) agalsidase beta-treated patients. There were no deaths. CONCLUSIONS: Based on rate of eGFR decline over 2 years, pegunigalsidase alfa was non-inferior to agalsidase beta. Pegunigalsidase alfa had lower rates of treatment-emergent adverse events and mild or moderate infusion-related reactions. TRIAL REGISTRATION NUMBER: NCT02795676.
Keywords: Drug-Related Side Effects and Adverse Reactions; Humans; lidé středního věku; Glomerular Filtration Rate; Female; mladý dospělý; dospělí; alfa-galaktosidasa; výsledek terapie; lidé; Recombinant Proteins; enzymová substituční terapie; hodnoty glomerulární filtrace; Genetic Diseases, Inborn; Fabryho nemoc; Adult; rekombinantní proteiny; Isoenzymes; ženské pohlaví; alpha-Galactosidase; Male; izoenzymy; Middle Aged; Adolescent; Treatment Outcome; Young Adult; Genetic Diseases, X-Linked; Enzyme Replacement Therapy; mužské pohlaví; Fabry Disease; mladiství